A Legacy in Fossils: a Tribute to Stan(ley) Wood – Preface. (March 2017) - Fraser, Nicholas C.; Smithson, Timothy R.; Clack, Jennifer A.
ABSTRACT: Stan Wood had a gift for finding exceptional Early Carboniferous fossils. Among them are 32 type specimens. His discoveries significantly changed our understanding of the history of life on Earth. Many of the fossils he collected are on display in museums across the UK and the localities he discovered continue to yield important new material. Here we briefly review some of Stan Wood's key achievements and describe the legacy he left.